CONCEPTUAL PRINCIPLES OF CREATING AN INNOVATIVE AGROCLUSTER IN CONDITIONS OF SUSTAINABLE DEVELOPMENT OF THE NATIONAL ECONOMY - Кошкалда, Ірина; Прокопишин, Оксана; Трушкіна, Наталія (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
At present, the agricultural sector of Ukraine is undergoing radical organizational changes and transformations in various areas of development, including innovation. This requires the formation and functioning of appropriate innovation infrastructure and the search for fundamentally new organizational and legal forms of management that would meet modern economic conditions. One such form may be an innovative agricultural cluster. The purpose of this study is to substantiate the conceptual basis for the creation of innovative agricultural clusters as an important component of the innovation ecosystem in terms of sustainable development. The article analyses and summarizes the legislative documents governing the creation and operation of innovative agricultural clusters as a new subject of economic and legal relations in the agricultural sector. Strategic programs of regional development till 2027 in the part of the creation of cluster structures are considered. The structural scheme of interaction of elements of the regional innovation ecosystem for the achievement of the strategic purpose “Innovative development of the region on the basis of smart specialization” is offered. Proposals on possible organizational and legal forms of the innovative agricultural cluster are presented, taking into account the best European practice. The differences between the cluster from other organizational and legal forms of business associations are determined. As a result of the research, it was established that the legislation does not pay due attention to the creation and functioning of innovation clusters in Ukraine. But in terms of prospects and effectiveness, clustering should be considered a key direction in the transformation of innovative management systems for the development of the agro-industrial complex. Therefore, the definition of the terms “cluster”, “clustering”, and “innovation cluster” in the agricultural sector remains an urgent issue. It is proposed to amend the laws of Ukraine “On Innovation”, “On Priority Areas of Innovation in Ukraine”, “On Scientific and Scientific-Technical Activities”, “On State Support of Agriculture of Ukraine”, Concepts of Clusters in Ukraine, Strategy development of the sphere of innovation activity for the period up to 2030, the State Strategy of Regional Development for 2021-2027 on the creation of an innovation cluster as a specific type of associations of enterprises in the agricultural sector.